The Effect of Student Digital Literacy on Radicalism Attitudes at PTKIN in Aceh - Nina Eka Putri (CV. Pusdikra Mitra Jaya, 2023)
Radicalism is an issue that has been frequently discussed in recent years, especially for Indonesia, which has five official religions, of course, interreligious contact is inevitable. Then, exposure to intolerance and radicalism is related to the development of information technology. Therefore, researchers conducted a study entitled The Influence of Student Digital Literacy on Radicalism Attitudes at PTKIN in Aceh. This study examines how the digital literacy of students at PTKIN in Aceh and the image of radicalism among students at PTKIN in Aceh, as well as how the influence of student digital literacy on attitudes of radicalism at PTKIN in Aceh. Then, this study used a mix methods approach with an explanatory design strategy and the techniques used in data collection were observation, questionnaires, and interviews. Next, from the results of the study it was found that (1) the level of digital literacy skills of students at PTKIN in Aceh has shown a high literacy ability of 82% with details of the ability level in terms of aspects of searching on the internet by 89%, aspects of text guides by 72%, the content evaluation aspect is 88%, and for the preparation aspect is 78%. (2) The results related to student attitudes towards radicalism show that in terms of cognitive response it tends to be high, namely 87% have heard of radicalism and the most widely obtained source is from social media, then in terms of affective response students tend to be moderate and tolerant , and in terms of conative responses students also tend to think moderately and stay away from actions that lead to radicalism. Finally, (3) the level of students' digital literacy ability has an influence on the attitude of radicalism at PTKIN in Aceh which is shown by the results of the level of student digital literacy ability which is higher than the attitude of radicalism possessed.